2003
DOI: 10.1542/peds.112.4.829
|View full text |Cite
|
Sign up to set email alerts
|

Healing Patterns in Anogenital Injuries: A Longitudinal Study of Injuries Associated With Sexual Abuse, Accidental Injuries, or Genital Surgery in the Preadolescent Child

Abstract: Anogenital trauma heals quickly, often without residua. Of the 94 cases, there were diagnostic anatomic changes in the 15 cases of hymenal transections (2 other cases healed completely with surgical reconstruction), 6 cases after surgical repair of posterior fourchette, and 2 cases of anal scarring after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0
10

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(94 citation statements)
references
References 20 publications
2
81
0
10
Order By: Relevance
“…[31][32][33] Many types of abuse leave no physical evidence, and mucosal injuries often heal rapidly and completely. [34][35][36][37][38] In a recent study of pregnant adolescents, only 2 of 36 had evidence of penetration. 39 Occasionally, a child presents with clear evidence of anogenital trauma without an adequate history.…”
Section: Diagnostic Considerationsmentioning
confidence: 99%
“…[31][32][33] Many types of abuse leave no physical evidence, and mucosal injuries often heal rapidly and completely. [34][35][36][37][38] In a recent study of pregnant adolescents, only 2 of 36 had evidence of penetration. 39 Occasionally, a child presents with clear evidence of anogenital trauma without an adequate history.…”
Section: Diagnostic Considerationsmentioning
confidence: 99%
“…Changes in the depth and configuration of the hymenal laceration continued for up to 3 weeks in prepubertal and 4 weeks in adolescent girls. Heppenstall-Heger et al [3] in contrast found that a transection did not heal without residua unless it had been surgically repaired.…”
Section: Healing Of Genital Injury Following Sexual Abusementioning
confidence: 95%
“…Anal fissürlerin sadece istismarla değil, kabızlık gibi tıbbi nedenlerle de meydana gelebileceği unutulmamalıdır. 18 Cinsel istismar tanısının konulacağı merkezde çalışacak uzman çocuğun normal anatomisini, cinsel istismar bulgularını taklit eden patolojik durumları ve cinsel istismar bulgularını bilmek zorundadır. Aksi takdirde yanlış tanı çocuk, aile ve şüpheli açısından onarılamaz zararlara neden olacaktır.…”
Section: İstati̇sti̇ksel Anali̇zunclassified